Navigating Educational Change in China Contemporary History and Lived Experiences - Wang, Fang (Curriculum Studies Worldwide, 2018)
This book is a reflection on the complexity of educational change in China through the lens of a senior academic who has occupied many diverse roles in the academe, from political worker to dean of faculty. It narrates his journey through different layers of historical, societal, and institutional transformation while trying to make sense of his own life and work. In this book, the professor is situated at the intersection of history, culture, and society where the search for personal identity becomes a lifelong project. Landmarks in his intellectual journey are used to elucidate the effects of early influences, significant others, challenges and opportunities, human agency, and professional capital. His story illustrates the vicissitudes of a long career that combines scholarship and administration, and offers lessons for survival, advancement, and leadership in the fluid environment of Chinese higher education institutions. .